Medications for Chronic Conditions and Mortality in Older Adults. Issue 1 (2nd January 2023) - Hsu, Hui-Fen; Tu, Hung-Pin; Chen, Kuei-Min; Belcastro, Frank
Abstract : Background: With the population aging, examining the relationship between polypharmacy and mortality based on population data sources is important for clinical management and policy direction. Objectives: This study aimed to examine the association between the number of chronic medications and the risk of mortality in older adults. Methods: This population-based retrospective cohort study used data from the National Health Insurance Research Database in Taiwan for information regarding chronic medication use (over 4 years) in older adults aged 65 years and older. The association between medication use and mortality numbers was analyzed using Cox proportional hazards regression models adjusted for demographic variables and comorbidity. Results: The number of medications was significantly associated with high mortality risk. Within polypharmacy, being 65–74 years old, male, living in northern Taiwan, having one type of comorbid disease, and receiving <84 days of refillable chronic prescription were associated with greater mortality risk. Subgroup analyses' results regarding comorbidity showed significant positive associations between the number of medications and mortality in most comorbid diseases except for mental disorders and diseases of the skin and subcutaneous tissue. Discussion: General practitioners should know that chronic polypharmacy is associated with increased mortality risk. Recognizing the possible adverse effects of multiple medication use could help physicians optimize drug regimens in the future.